A case with posterior fossa epidermoid cyst showing audiovestibular symptoms caused by insufficiency of anterior inferior cerebellar artery - usefulness of free DICOM image viewing and processing software. - Takasaki K; Kumagami H; Baba A; Fujiyama D; Takahashi H (Acta Oto-Laryngologica (Supplement))
A 58-year-old Japanese man suddenly suffered from vertigo. On physical examination, left-beating horizontal torsional spontaneous nystagmus was observed; the direction did not change with gaze. Other neurotological examinations revealed findings within normal limits except the left side sensorineural hearing loss of approximately 32 dB on average. Diffusion-weighted MRI revealed no infarction in the brain, but demonstrated an epidermoid cyst in the left cerebello-pontine cistern region. Using free digital imaging and communications in medicine (DICOM) image viewing and processing software, it was found that the epidermoid cyst clearly compressed the left anterior inferior cerebellar artery (AICA). Therefore, we speculated that insufficiency of the left AICA caused his audiovestibular symptoms. This new technique used in the present study was considered useful when the site responsible for vertigo is suspected in the cerebello-pontine angle, where anatomic relationships between the nerves and the vessels are complicated.